Financial Independence and Academic Achievement: Are There Key Factors of Transition to Adulthood for Young Higher Education Students in Colombia? - Borjas, Mónica-Patricia; Ricardo, Carmen; Escalante-Barrios, Elsa Lucia; Valencia, Jorge; Aparicio, Jose (Frontiers in Psychology, 2020)
Autonomy is conceptualized as the need for agency, self-actualization and independence. Nowadays, financial independence and academic achievement for young populations may be considered as key aspects in the transition to adulthood in response to some contextual demands of different cultural environments. By means of a multi-level model, the present study aims to determine the influence and contribution of factors at individual-level (e.g. sex, age, socioeconomic status, family financial support, awarded scholarships, personal finance, student loans) and school-level (e.g. programme quality, online programs, face to face programs) on the academic achievement of young higher education Colombian students. Data come from the scores of the national standardized academic achievement test administered in 2018 in Colombia. The sample included 234,386 students enrolled in 3,389 higher education institutions in Colombia. After controlling the effects of program quality, and the student's previous academic abilities and socio-economic conditions, results showed that students with scholarships had higher scores than financially-dependent students (those who had students loans) and financially-independent students (those who self-funded their studies or who worked during the week) who had low-scores in the national standardized academic achievement test.